Service Strengthening Strategy Primary Through Engagement Health Cadres in The Community - Subhi, Imam; Cahyati, Widya Hary; Zainafree, Intan (Universitas Negeri Semarang, 2025)
Background: Strengthening primary and community health systems is crucial in improving population health, particularly in developing countries. Various studies have emphasized the importance of healthcare workers, such as physicians, physical therapists, and community health workers (CHWs), in promoting equitable and effective health service delivery. This study aims to analyze the roles, challenges, and innovations in developing primary and community health systems in resource-limited settings. Methods: This study employed a narrative literature review approach using peer-reviewed articles published between 2015 and 2023. Data sources included PubMed, Scopus, and ScienceDirect. Keywords used were “primary care,” “community health workers,” “health system strengthening,” and “developing countries.” Thematic analysis was conducted to identify patterns, innovations, and policy implications. Results: The review found that CHWs significantly contribute to cost-effective care and improved service coverage in underserved areas. Innovations such as insurance administration-free models and participatory research-based interventions in South Africa were effective in enhancing decision-making among CHWs. Additionally, interventions for non-communicable diseases (e.g., hypertension, diabetes) and pediatric oncology in Sub-Saharan Africa demonstrated the need for tailored health strategies. In the education sector, the integration of mental health and research ethics training for healthcare workers in South Africa and Uganda reinforced the importance of investing in human resources for health. Conclusion: The findings underscore the importance of empowering healthcare workers, implementing innovative service delivery models, and enhancing health education systems. Strengthening public health systems requires collaborative policy efforts and sustained investment to promote health equity and resilience, especially in low-resource settings.